UMA CONTRIBUIÇÃO PARA O ESTUO DO PANORAMA HÍDRICO DA AMAZÔNIA - Castro, Veronica Vasconcelos de (2003)
The present paper intends to contribute for the study of the hydrical outlook of the Amazon Region. It was realized a study of the hydrical resources management models implanted in other to establish comparative parameters with the management model in our country at the present time. The Amazon Region was the propose of the study, focusing the points related to the management, achieving as a result a guideline proposal directly related to this area that present its own features. A hydrical resource management nationally integrated is what this paper proposes, however it is also necessary to focus the region problems, in order to be efficient